1977
DOI: 10.1099/00222615-10-1-49
|View full text |Cite
|
Sign up to set email alerts
|

The Anaerobic Culture of Clinical Specimens: A 14-Month Study

Abstract: THE isolation rate of anaerobic bacteria from clinical specimens increased manyfold in our laboratory when the techniques for anaerobic bacteriology were revised. We present here an account of our findings with these methods applied as a routine to clinical specimens, and make recommendations concerning the techniques of incubation, media and the use of certain identification tests. The isolation of anaerobic species from different anatomical sites is described, and special attention is given to the yield of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 13 publications
1
31
0
Order By: Relevance
“…multocida nor any other organism isolated appeared to play a dominant role in the production of the subcutaneous abscesses that we examined. The many recent studies in which modern anaerobic-culture techniques were used have revealed the diversity of human infections that are caused by anaerobes or mixtures of anaerobes (Finegold, 1974;Gorbach, 1974;Wren et al, 1977). In such human infections, gram-negative anaerobic bacilli were the most common isolates and B. fragilis was the species most commonly encountered.…”
Section: Discussionmentioning
confidence: 99%
“…multocida nor any other organism isolated appeared to play a dominant role in the production of the subcutaneous abscesses that we examined. The many recent studies in which modern anaerobic-culture techniques were used have revealed the diversity of human infections that are caused by anaerobes or mixtures of anaerobes (Finegold, 1974;Gorbach, 1974;Wren et al, 1977). In such human infections, gram-negative anaerobic bacilli were the most common isolates and B. fragilis was the species most commonly encountered.…”
Section: Discussionmentioning
confidence: 99%
“…13 Isolates were identified conventionally13 14 and antibiotic sensitivities obtained by the comparative method using discs.…”
Section: Methodsmentioning
confidence: 99%
“…In all, 50% of the isolates were anaerobic gramnegative bacilli and a further 33.6% of the strains were anaerobic cocci. DISCUSSION Earlier work in this laboratory revealed that significantly greater numbers of anaerobic bacteria can be recovered from clinical specimens cultured on primary anaerobic plates if the plates are incubated for 48 h rather than 24 h before being examined for the first time (Wren et al, 1977).…”
Section: Resultsmentioning
confidence: 99%